ANALISIS TINGKAT LITERASI KEUANGAN SYARIAH MASYARAKAT KECAMATAN PANTI - Riska Khairani; Rusydi Fauzan (CV. Adiba Aisha Amira, 2023)
This study aims to assess people's familiarity with sharia-compliant financial management in Kecamatan Panti.Aspects of syrian financial literature included in this study include syrian basic financial knowledge, syrian savings and loan, syrian insurance, and syrian investment. The research methods employed are quantitative in nature, with a focus on field research.In this study, we surveyed the population of Kecamatan Panti, which ranged in age from 20 to 39.A total of 84 people were sampled for this study using a solvin sampling technique.Data analysis was performed using a descriptive statistical method. This study's findings suggest that residents of Panti, Indonesia have an overall level of financial literacy somewhere around 74.64%, with 74.64% falling inside the